A debate on current eating disorder diagnoses in light of neurobiological findings: is it time for a spectrum model? - Brooks Samantha; Rask-Andersen Mathias; Benedict Christian; Schiöth Helgi (BMC Psychiatry, 2012)
Abstract Background Sixty percent of eating disorders do not meet criteria for anorexia- or bulimia nervosa, as defined by the Diagnostic and Statistical Manual version 4 (DSM-IV). Instead they are diagnosed as ‘eating disorders not otherwise specified’ (EDNOS). Discrepancies between criteria and clinical reality currently hampering eating disorder diagnoses in the DSM-IV will be addressed by the forthcoming DSM-V. However, future diagnoses for eating disorders will rely on current advances in the fields of neuroimaging and genetics for classification of symptoms that will ultimately improve treatment. Discussion Here we debate the classification issues, and discuss how brain imaging and genetic discoveries might be interwoven into a model of eating disorders to provide better classification and treatment. The debate concerns: a) current issues in the classification of eating disorders in the DSM-IV, b) changes proposed for DSM-V, c) neuroimaging eating disorder research and d) genetic eating disorder research. Summary We outline a novel evidence-based ‘impulse control’ spectrum model of eating disorders. A model of eating disorders is proposed that will aid future diagnosis of symptoms, coinciding with contemporary suggestions by clinicians and the proposed changes due to be published in the DSM-V.